Single-cell transcriptomic profiling reveals a novel signature of necrotizing granulomatous lesions in the lungs of Mycobacterium tuberculosis-infected C3HeB/FeJ mice - Seto, Shintaro; Omori, Shiho; Nakamura, Hajime; Hijikata, Minako; Keicho, Naoto (Frontiers in Immunology, 2025)
Tuberculosis (TB) pathology involves complex immune responses within granulomatous lesions. Using single-cell RNA sequencing, we characterized the cellular compositions of necrotizing granulomatous lesions that developed in the lungs of Mycobacterium tuberculosis-infected C3HeB/FeJ mice. We identified 11 distinct major cell types, including phagocytes such as neutrophils and macrophages, and T cells, natural killer cells, B cells, dendritic cells, and plasmacytoid dendritic cells. Among T cells, particularly, Pdcd1+ γδ T cells were detected in necrotizing granulomatous lesions, suggesting their potential role in the pathogenicity of M. tuberculosis. Within the macrophage populations, we identified a cluster with significantly higher Plin2 expression compared to other clusters, whose transcriptomic profile was consistent with that of foamy macrophages. A subset of the Plin2-expressing macrophages was identified as a major source of Ifnb1 and Cxcl1, suggesting their involvement in type I interferon signaling and neutrophil recruitment. Furthermore, we identified Flrt2, Hyal1, and Mmp13 as novel molecular markers of Plin2-expressing macrophages, which were localized to the peripheral rim regions of necrotizing granulomas. In conclusion, our results provide the immune landscape of necrotizing granulomas and reveal novel functional states of macrophages contributing to TB pathogenesis.